2017
DOI: 10.1111/odi.12742
|View full text |Cite
|
Sign up to set email alerts
|

Association of sickle cell haemoglobinopathies with dental and jaw bone abnormalities

Abstract: Pulp calcification and external resorption of the root were the most frequent dental alterations in sickle cell anaemia group, while in trait was higher frequency of changes in shape, size, periapex and root. Jaw bone changes were most prevalent in both homozygous and heterozygous subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…She was determined to have a periosteal, localized effusion in the right masticator space, but no odontogenic lesion, and did well with noninvasive management. While previous reports have described this phenomenon,7–10 few reports were in the pediatric population, as recently reviewed 10,11. Sickle vaso-occlusive episodes can be associated with fever without infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She was determined to have a periosteal, localized effusion in the right masticator space, but no odontogenic lesion, and did well with noninvasive management. While previous reports have described this phenomenon,7–10 few reports were in the pediatric population, as recently reviewed 10,11. Sickle vaso-occlusive episodes can be associated with fever without infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic damage to bone is commonly recognized in the femoral and humeral heads and vertebral bodies, which are leading causes of disability and hospitalizations 5–7. A growing recognition from dental radiographs demonstrate that the mandible and maxilla also suffer ischemic changes, manifested as diminished density of the trabeculae 7,8. Patients with SCD commonly experience vaso-occlusive crisis (VOC) in the lower back, upper and lower extremities, but it is less common for them to experience VOC in the facial bones and oropharynx, especially in the pediatric population 7–10.…”
Section: Introductionmentioning
confidence: 99%
“…The literature reveals debatable results regarding the protective role of medications, particularly antibiotics, received by these patients against dental caries [25], [30]. Several studies have shown higher prevalence of malocclusion problems in SCD pediatric patients than healthy controls [60]- [66] and others support that SCD is being related with the occurrence of other orofacial manifestations, such as soft tissue and bone changes [38], [39], [44], [50], [53], [57], [72]- [75], [77], [79], [80], [83]. Individuals with SCD have reported difficulty in accessing primary dental care due to refusal of some dentists to treat these patients under fear of complications [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, this abnormal blood flow and pulpal hypoxia may result in pulpal pain in SCD patients with the absence of any other dental pathology [6], [79]. Additionally, studies have reported pulp calcification [73], [80], denticle-like calcifications and an increased number of stones in the pulp in SCD patients [74].…”
Section: Pulp Necrosismentioning
confidence: 99%
“…This can be mistaken for external root resorption, which incidentally has increased prevalence in those affected by SCA. 6 We suspect that the patient has been experiencing multiple episodes of vaso-occlusive events affecting the teeth and supporting structures. We have liaised with the consultant haematologist whom the patient is under the care of in order to make them aware of this aspect of the patient's disease.…”
mentioning
confidence: 99%